Rice panicle detection from unmanned aerial vehicle (UAV) imagery via image restoration and pseudo-depth prior - Pan Pan; Haochun Li; MingXia Li; Saiyang Xu; Zhihao Guo; Guoping Yu; Long Yi; Maomao Li; Guomin Zhou; Jianhua Zhang (Computers and Electronics in Agriculture, 2026)

Physics-guided bidirectional synergistic fusion network for stern bearing fault diagnosis in ship propulsion systems - Hongdi Zhou; Yong Pan; Tielin Shi; Jian Duan; Chao Qian; Guoping Yan; Yijie Cai (Ocean Engineering, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

A one-stone-three-birds strategy: Manipulating sodiation depth of SnTe anode enabling fast ion conduction, shuttle avoidance, and sodium replenishment for durable sodium-ion batteries - Zhiming Jia; Guoping Liu; Xu Han; Gangyong Zhou; Haihui chen; Chunjiang Jin; Ting Liu; Lingfeng Xu; Renyun Kuang; Changwang Pan; Shengping Dai; Dingwa Zhang; et al. (Chemical Engineering Journal, 2026)

China’s participation and response to IMO legislation on shipping decarbonization: an analysis based on environmental regulatory approaches - Guoping Xu; Xinzhu Pan (Frontiers in Marine Science, 2026)
In recent years, to align the shipping industry with the temperature goals of the Paris Agreement and address climate change, the International Maritime Organization (IMO), which regulates international shipping, together with regional international organizations and countries responsible for shipping within their respective jurisdictions, has continuously strengthened the governance of shipping decarbonization. As a branch of environmental law, the governance of shipping decarbonization at both the international and domestic level involves multiple stakeholders and various environmental regulatory approaches. This article uses the main classification of environmental regulatory approaches as an analytical framework to examine the interactions between China and the IMO in this area. Specifically, this review addresses the following key aspects: (1) China’s participation in IMO’s legislation as a strong advocate for the principle of common but differentiated responsibilities and respective capabilities, as well as in the formation of the Regulations on IMO Net-Zero Framework (NZF), new draft amendments to MARPOL Annex VI, which was not adopted as originally scheduled but represents a milestone in the IMO’s efforts to form a GHG emissions pricing mechanism and to advance shipping decarbonization through the integration of multiple environmental regulatory approaches. (2) China’s domestic governance for shipping decarbonization, which likewise incorporates multiple environmental regulatory approaches in response to the IMO’s work and in pursuit of its ‘dual carbon’ targets. (3) Challenges and opportunities the IMO’s NZF presents for China. (4) Recommendations for strengthening China’s governance of shipping decarbonization to respond to the NZF while further advancing its ‘dual carbon’ target.

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

Synergistic interfacial shielding in Ni6MnO8/Zn0.5Cd0.5S heterostructures enables enhanced photocorrosion resistance and solar-driven hydrogen evolution - Kang liu; Fei Jin; Xinyu Pan; Yuyu Wang; Guoping Jiang; Zhiliang Jin (Chemical Engineering Journal, 2026)

Crafting cellulose hollow microspheres with cellulose nanosheets - Wenxuan Lei; Heng Huang; Ruobing Liang; Guoping Li; Pan Chen; Jiechun Xiang; Ang Lu (Carbohydrate Polymers, 2026)

Polyvalent immunoprotection of protein, DNA and IgY antibody vaccines of Vibrio fluvialis outer membrane protein VF08100 in fish - Huihui Xiao; Saixing Duan; Pan Cui; Jing Chen; Xixian Che; Juan Lu; Juan Wang; Guoping Zhu; Yong Liu; Xiang Liu (Fish & Shellfish Immunology, 2025)

In-situ hybrid armor layer enabled by additive-anion synergy for dendrite-free and stable Zn anode - Yu Han; Yufei Xue; Teng Wang; Chiyu Zhang; Fuping Pan; Taotao Ai; Wenhu Li; Wei Ai; Guoping Gao; Kai-Jie Chen (Chemical Engineering Journal, 2025)

Grapefruit essential oil combined with UV-C treatment: A technology to improve the microbial safety of fresh produce - Ningbo Liao; Xinyun Chen; Mengxuan Tang; Peng Tian; Chengwei Liu; Lu Ruan; Hong Pan; Mei Shu; Chan Zhong; Guoping Wu (Innovative Food Science & Emerging Technologies, 2024)

Evaluation of annual production and economic benefits of tropical rice-crayfish coculture system in China - Yifan Li; Xucan Ku; Shaodong Wang; Guoping Pan; Qiyun Xu; Hongyan Liu; Jiaolong Li (Agricultural Systems, 2024)

Insight into the humification and carbon balance of biogas residual biochar amended co-composting of hog slurry and wheat straw - Yunpeng Liu; Junting Pan; Jingwen Wang; Xu Yang; Wanqiang Zhang; Kuok Ho Daniel Tang; Hailong Wang; Xiu Zhang; Runyu Gao; Guoping Yang; Zengqiang Zhang; Ronghua Li (Environmental Science and Pollution Research, 2024)

Integrating ecosystem services closely related to human well-being into the restoration and management of deep lakes facing multiple stressors: Lessons from long-term practice in Qiandao Lake, China - Zhen Zhang; Qigen Liu; Guoping Gao; Jianqiang Shao; Jiayong Pan; Guangxi He; Zhongjun Hu (Science of The Total Environment, 2023)

Sample Collection, DNA Extraction, and Library Construction Protocols of the Human Microbiome Studies in the International Human Phenome Project - Yetong Wang; Ruyi Zhang; Yanni Pu; Danqi Wang; Yanren Wang; Xuemei Wu; Yujie Pan; Chen Luo; Guoping Zhao; Zhexue Quan; Yan Zheng (Phenomics, 2023)

Insight into boron-doped biochar as efficient metal-free catalyst for peroxymonosulfate activation: Important role of -O-B-O- moieties - Guoping Pan; Jia Wei; Mengdie Xu; Jiamei Li; Linhao Wang; Yanan Li; Nan Cui; Jun Li; Zhaoxu Wang (Journal of Hazardous Materials, 2023)

Electron transfer mechanism mediated nitrogen-enriched biochar encapsulated cobalt nanoparticles catalyst as an effective persulfate activator for doxycycline removal - Zijian Jiang; Jia Wei; Yifei Zhang; Xiruo Niu; Jiamei Li; Yanan Li; Guoping Pan; Mengdie Xu; Xueru Cui; Nan Cui; Jun Li (Journal of Cleaner Production, 2023)

High-efficiency electro-Fenton process based on in-situ grown CoFeCe-LDH@CFs free-standing cathodes: Correlation of cerium and oxygen vacancies with H2O2 - Mengdie Xu; Jia Wei; Xueru Cui; Jiamei Li; Guoping Pan; Yanan Li; Zijian Jiang; Xiruo Niu; Nan Cui; Jun Li (Chemical Engineering Journal, 2023)

A botanical medicine dragon’s blood exhibited clinical antithrombosis efficacy similar to low molecular weight heparin - Jiangbin Liang; Song Mei; Xiangyu Qiao; Wei Pan; Yan Zhao; Shaohui Shi; Yaling Zhai; Haizhao Wen; Guoping Wu; Chengyu Jiang (Science China Life Sciences, 2021)

Genetic and clinical determinants of mizoribine pharmacokinetics in renal transplant recipients - Rui Dai; Jingjie Li; Jingjing Wu; Qian Fu; Jiajia Yan; Guoping Zhong; Changxi Wang; Xiao Chen; Pan Chen (European Journal of Clinical Pharmacology, 2021)

Molecular Characterization of Six Tissue-Specific or Stress-Inducible Genes of NAC Transcription Factor Family in Tomato (Solanum lycopersicum) - Mingku Zhu; Zongli Hu; Shuang Zhou; Lingling Wang; Tingting Dong; Yu Pan; Guoping Chen (Journal of Plant Growth Regulation, 2014)

The abiotic stress-responsive NAC-type transcription factor SlNAC4 regulates salt and drought tolerance and stress-related genes in tomato (Solanum lycopersicum) - Mingku Zhu; Guoping Chen; Jianling Zhang; Yanjie Zhang; Qiaoli Xie; Zhiping Zhao; Yu Pan; Zongli Hu (Plant Cell Reports, 2014)

An ethylene response factor (ERF5) promoting adaptation to drought and salt tolerance in tomato - Yu Pan; Graham B. Seymour; Chungui Lu; Zongli Hu; Xuqing Chen; Guoping Chen (Plant Cell Reports, 2012)

Functional analysis of tomato LeEIL1 in an Arabidopsis ein2 mutant - Yu Pan; Guoping Chen; Chungui Lu; Xuqing Chen; Zongli Hu (Acta Physiologiae Plantarum, 2011)

Characterization of Bombyx mori nucleopolyhedrovirus orf74, a novel gene involved in virulence of virus - Hongxing Shen; Keping Chen; Qin Yao; Wei Yu; Ye Pan; Juan Huo; Hengchuan Xia; Guoping Huang (Virus Genes, 2009)

Analyzing unsaturated flow patterns in fractured rock using an integrated modeling approach - Yu-Shu Wu; Guoping Lu; Keni Zhang; Lehua Pan; Gudmundur S. Bodvarsson (Hydrogeology Journal, 2007)

Identification and characterization of odv-e25 of Spodoptera litura multicapsid nucleopolyhedrovirus - Zhaofei Li; Lijin Pan; Hang Yu; Sainan Li; Guoping Zhang; Yi Pang (Virus Genes, 2006)

Characterization of Heavy Metals and Sulphur Isotope in Water and Sediments of a Mine-Tailing Area Rich in Carbonate - Guoping Zhang; Cong-Qiang Liu; Yuangen Yang; Pan Wu (Water, Air, & Soil Pollution, 2004)